THE ROLE OF FAMILY IN JOHN STEINBECKâS THE GRAPES OF WRATH - Setyabudi, Titis (Kajian Linguistik dan Sastra, 2011)
This is an analysis of John Steinbeckâs novel The Grapes of Wrath conductedÂ using structuralism approach. The result shows that the meaning of family in TheÂ Grapes of Wrath has two supporting dimensions. First, a family is nuclear familyÂ consisting of a father, mother and children. They live as a household and in oneÂ house. Sometimes, they consider extended family particularly grandfather, grandmother, uncles, and others. Second, a family is a group of people with same backgrounds and problems. In The Grapes of Wrath, the meaning of family dramatically is gained from their family bond and togetherness at Route 66.Key words: Family, Structuralism, The Grapes of Wrath, John Steinbeck